Boom and bust a global history of financial bubbles - William Quinn and John D. Turner (New York Cambridge University Press, 2020)
"Why do stock and housing markets sometimes experience amazing booms followed by massive busts and why is this happening more and more frequently? In order to answer these questions, William Quinn and John D. Turner take us on a riveting ride through the history of financial bubbles, visiting, among other places, Paris and London in 1720, Latin America in the 1820s, Melbourne in the 1880s, New York in the 1920s, Tokyo in the 1980s, Silicon Valley in the 1990s and Shanghai in the 2000s. As they do so, they help us understand why bubbles happen, and why some have catastrophic economic, social and political consequences whilst others have actually benefitted society. They reveal that bubbles start when investors and speculators react to new technology or political initiatives, showing that our ability to predict future bubbles will ultimately come down to being able to predict these sparks"-- Provided by publisher.
Includes bibliographical references and index
Keywords: Business cycles--History.